2022
DOI: 10.3390/w14213506
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Influence of Biochar and Zeolite on Soil Hydrological Indices and Growth Characteristics of Corn (Zea mays L.)

Abstract: Biochar and zeolite, due to their porous structure, are supposed to be appropriate soil amendments especially in agricultural areas with a lack of water or unsuitable soils with coarse texture. Two soil additions that are intended to assist an increase soil water content (AWC) are biochar and zeolite. With this aim, the effects of biochar and zeolite at two levels of 5 and 10 t ha−1 (known as B5, B10, Z5, and Z10) on soil hydrological properties and consequently corn growth were investigated in this study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 83 publications
4
11
0
Order By: Relevance
“…Contrariwise, the application of silicon, zinc, and zeolite evidently reduced leaf chlorophyll degradation and increased SC and Fv/Fm and photosynthetic apparatus of drought-stressed plants [41][42][43][44][45]. These findings could be related to the ability of the previous nano-treatments to alleviate the negative impacts of drought by enhancing hydraulic conductivity, conserving higher transpiratory and photosynthesis rates, photosynthetic pigment concentrations, and reducing oxidative damages [46,47]. Furthermore, the improvement in total carbohydrate content in drought-stressed plants supplied with N-silicon, N-zinc, and N-zeolite could be associated with elevating the photosynthesis rate and CO 2 assimilation, as shown in Figure 2D [20,41,[48][49][50]].…”
Section: Discussionmentioning
confidence: 88%
“…Contrariwise, the application of silicon, zinc, and zeolite evidently reduced leaf chlorophyll degradation and increased SC and Fv/Fm and photosynthetic apparatus of drought-stressed plants [41][42][43][44][45]. These findings could be related to the ability of the previous nano-treatments to alleviate the negative impacts of drought by enhancing hydraulic conductivity, conserving higher transpiratory and photosynthesis rates, photosynthetic pigment concentrations, and reducing oxidative damages [46,47]. Furthermore, the improvement in total carbohydrate content in drought-stressed plants supplied with N-silicon, N-zinc, and N-zeolite could be associated with elevating the photosynthesis rate and CO 2 assimilation, as shown in Figure 2D [20,41,[48][49][50]].…”
Section: Discussionmentioning
confidence: 88%
“…To cite some examples, [50] observed no effects of clinoptilolite zeolite addition to acidic pasture and wetland soils while [37] observed a slight but significant alkalinization effect (from 5.27 to 5.66) 3 days after the addition of N-enriched chabazite in the same acidic sandy soil used in this study. No significant effect of clinoptilolite zeolite addition was reported by [51] while [52] observed a slight increase in soil pH after adding zeolites, from 4.69 to 4.92 and from 6.13 to 6.39 in the two different soils. Some authors explained this pH alkalinization both by the alkaline pH of the used zeolites (in some studies the clinoptilolite showed a pH > 8.0 in H 2 O) or by the adsorption of H + from the soil solution which can lead to a temporary rise in soil pH.…”
Section: Effects Of the Different N Sourcesmentioning
confidence: 87%
“…Compared to other silicate minerals, the spacious porous structure with large channels in bentonite and zeolite could positively affect the exchange capacity of cations (CEC, 200-300 meq 100 −1 g) and subsequently promote the substitution of ions and reduce the contents of salt [31]. However, a recent study showed that the soil SAR in zeolite-treated soils increased by 65% and 143% [32]. This could be due to the different soil types used in the former studies (sandy loam saline) and this (clay loam saline) study.…”
Section: Application Of Porous Minerals Ameliorated Soil Properties I...mentioning
confidence: 99%